Design of a machine for cleaning chiffon cake tins - Lim, Louis Qi Rui (2014)
This project set out to find a method to efficiently and automatically clean chiffon cake tins which are caked with stubborn stuck-on bits after baking. Two methods were investigated: the use of ultrasound and water jet. The ultrasound method was found to be impractical as the stuck-on bits remain attached to the tins even after exposure to ultrasound. Water jet can be very effective, but it’s dependent on the power and angle of the jetting pressure. A compact machine was then designed for water jet cleaning, incorporating automatic feeding of the tins before cleaning and the dispensing of the tins after. The coverage of the jet over the whole tin is affected by rotating motion of the tin on a rotary table by the power of the jetting pressure, therefore not relying on the need for a motor to rotate the table. The mechanisms of the machine is simulated on the computer using a dynamic simulation system. Due to time constraint, no prototype has been fabricated. So one of the future recommendation is to develop the prototype, during which further improvements can be investigated and made to the design itself.